Legaсy of the great plan of environment transformation in Russia - Mazurov, Yu.L.; Slipenchuk, M.V. (KU Publ., 2021)
In October 1948, a comprehensive long-term plan for the transformation of environment was adopted in the USSR in order to ensure maximum sustainable yields in the main agricultural regions of the country. The project, designed for the period 1949–1965, was developed as a reaction to the consequences of severe 1946 drought, but its content is undoubtedly a strategic document of national importance. The created forest belts and reservoirs had to significantly diversify the flora and fauna of the country. Consequently, the plan combines the tasks of environmental protection and obtaining maximum sustainable yields. The paramount feature of this plan was its thorough scientific support based on the ideas of a whole galaxy of prominent Russian scientists and practitioners. This plan anticipated the emergence of the national concept of rational nature management. It was not fully implemented. However, the very fact of its adoption and partial implementation has become a bright page in the history of domestic land use and an instructive example of a combination of economic, social and environmental interests. Numerous manifestations of this plan legacy in modern conditions are perceived as a multifunctional historical heritage that deserves a high national status.
Ресейдегі қоршаған ортаны трансформациялаудың ұлы жоспарының мұрасы
Наследие великого плана трансформации окружающей среды в России
Keywords: legacy; cultural landscapes; agriculture; nature management; environment transformation; heritage sites